PENGEMBANGAN RING BASKET UNTUK PEMBELAJARAN SHOOTING PADA PESERTA DIDIK SEKOLAH MENENGAH PERTAMA - Prasmita, Claudia; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem of this research was the students who did not able in basketball shooting with the standard of basketball ring height. This research were aim to create product of equipment basketball ring and to improve students’ learning motivation in learning of shooting basketball.The sampling technique used purposive sampling technique. The instrument of this research was the questionnaire with Gutman scale assessment and was validated of two experts by using delphi technique. The method of this research used research and development method which referring to development model of Borg & Gall. The data analysis technique that was used descriptive percentage. The slight scale trial was done at SMP Harapan Ananda and the extensive scale trial was done at SMP N 3 and SMP N 1 in Kuburaya.The trial result of equipment implementation (basketball ring) achieved 95% data with excellent category. The level of students’ acceptance toward product concept through five indicators; the size of equipment height 100%; the safety 93.4%; convenience 100%; strength 86.6%; and appearance 93.4%, all of categories included in accept category. Based on the result of research data, could be concluded that equipment product basketball ring proper be used in learning process of basketball shooting. Keywords: Basketball ring, Basketball Shooting, Learning.